2023
DOI: 10.1021/acsami.2c23008
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Cyclic Ether-Based Electrolytes for Low-Temperature Sodium-Ion Batteries

Abstract: Cyclic ethers are promising solvents for low-temperature electrolytes, but they still suffer from intrinsic poor antioxidant abilities. Until now, ether-based electrolytes have been rarely reported for high-voltage sodium-ion batteries (SIBs) operated under a low-temperature range. Herein, a novel ether-based electrolyte consisting of tetrahydrofuran as the main solvent is proposed and it could be utilized for a high-voltage Na2/3Mn2/3Ni1/3O2 (MN) cathode in a wide-temperature range from −40 to 25 °C. Meanwhil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The assembled Na 2/3 Mn 2/3 -Ni 1/3 O 2 ||Na cell with 0.8 M NaPF 6 -THF/PC/ethoxy(pentafluoro)-cyclotriphosphazene (PFPN) electrolyte could generate a thin and robust inorganic component-rich CEI layer for the stable cycling at a LT of −40 °C. 265 In addition, an artificial CEI layer with the desired components can be achieved by directly introducing Na 2 CO 3 and NaF as functional additives. 266 As for the cathode materials, the formation of a robust and homogeneous CEI layer is usually achieved by ion doping.…”
Section: Interface Chemistry For Harsh-temperature Applicationsmentioning
confidence: 99%
“…The assembled Na 2/3 Mn 2/3 -Ni 1/3 O 2 ||Na cell with 0.8 M NaPF 6 -THF/PC/ethoxy(pentafluoro)-cyclotriphosphazene (PFPN) electrolyte could generate a thin and robust inorganic component-rich CEI layer for the stable cycling at a LT of −40 °C. 265 In addition, an artificial CEI layer with the desired components can be achieved by directly introducing Na 2 CO 3 and NaF as functional additives. 266 As for the cathode materials, the formation of a robust and homogeneous CEI layer is usually achieved by ion doping.…”
Section: Interface Chemistry For Harsh-temperature Applicationsmentioning
confidence: 99%
“…Therefore, we developed a series of low-temperature ether-based electrolytes to further improve the performance. Ether solvents, especially cyclic ether, show great potential in low-temperature electrolytes because of the low freezing point and low viscosity; nevertheless, they easily polymerize in the presence of inorganic salt (e.g., NaPF 6 , LiPF 6 , and LiBF 4 , etc.). Specifically, in the presence of trace water, salt-like NaPF 6 decomposes into PF 5 , which then reacts with H 2 O to form protonic acid.…”
Section: Pw For Cold Climatesmentioning
confidence: 99%
“…[130] You et al proposed a novel ether-based electrolyte using tetrahydrofuran (THF) as the main solvent, and PC and ethoxy (pentafluoro) cyclophosphazene (PFPN) as the co-solvents. [131] The battery was assembled using Na 2/3 Mn 2/3 Ni 1/3 O 2 as the cathode and tested. The results indicated that compared to electrolytes using pure THF as the solvent, this new type of etherbased electrolyte not only improved the electrochemical stability of the material, but also formed a light, stable, and inorganic-rich CEI on the cathode material surface due to the presence of cosolvent PFPN.…”
Section: Cei On the Surface Of Prussian Blue Cathode Materialsmentioning
confidence: 99%
“…Even under low‐temperature conditions of −40 °C, CEI could promote the electrochemical performance of the cathode, with a capacity retention rate of 94.1% after 100 cycles at 0.2 C. These research developments offer new research directions for the design of stable SIB operation at extremely low temperatures. [ 131 ]…”
Section: Cei At Low Temperaturementioning
confidence: 99%